The Effect of Service Quality, Price Perception, And Brand Image on Customer Loyalty Through Customer Satisfaction of Grab Transportation in Bekasi City - Agus Harry Sujarwan; Teddy Oswari (Journal on Economics, Management and Business Technology, 2024)
PT Grab Teknologi Indonesia operates in the transport service sector as an intermediary between motorbike taxi drivers and customers. In addition, various additional features such as purchasing, payment, and delivery of goods also help in the shopping process with flexibility from various locations. The purpose of this study is to determine the effect of service quality, price perception, and brand image on customer loyalty through Grab customer satisfaction in Bekasi city. This study uses a population of Grab service users in Bekasi City, primary data, namely data conducted by distributing questionnaires to 120 respondents who use Grab services in Bekasi City. With the tests carried out are: validity test, reliability test, outer model measurement model (convergent validity, discriminant validity, composite reliability test), then there is a structural model or inner model (coefficient of determination R square, model fit evaluation), and finally there is hypothesis testing (path coefficient and specific indirect effect). The results of path analysis show that 1) Service quality and price perceptions directly have an insignificant effect on customer loyalty. 2) Brand image and customer satisfaction directly have a significant effect on customer loyalty. 3) Customer satisfaction directly has a significant effect on customer loyalty. 4) Service quality, perceived price, and brand image directly have a significant effect on customer satisfaction. 5) Service quality, price perception, and brand image have a significant effect on customer loyalty through customer satisfaction with a smaller / greater influence value than the direct effect (without going through intervening variables).